2020
DOI: 10.3389/fmicb.2020.587317
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 nsp1: Bioinformatics, Potential Structural and Functional Features, and Implications for Drug/Vaccine Designs

Abstract: The emerging coronavirus disease (COVID-19) caused by SARS-CoV-2 has led to social and economic disruption globally. It is urgently needed to understand the structure and function of the viral proteins for understanding of the viral infection and pathogenesis and development of prophylaxis and treatment strategies. Coronavirus non-structural protein 1 (nsp1) is a notable virulence factor with versatile roles in virus-host interactions and exhibits unique characteristics on sequence, structure, and function mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 58 publications
1
72
1
Order By: Relevance
“…While a previous study has established the crucial role played by N in viral genome processing and nucleocapsid assembly (Carlson et al, 2020), to the best of our knowledge there have been no prior reports specifically highlighting its ability to elevate lentiviral spike pseudovirus infectivity. It bears mentioning that similar to existent reports (Min et al, 2020;Schubert et al, 2020;Thoms et al, 2020;Lapointe et al, 2021;Zhang et al, 2021), the Nsp1 protein presumably exerts a detrimental effect on the host cell's protein translation, as indicated by the almost imperceptible extent of infectivity observed in its case (Figure 2A).…”
Section: Discussionsupporting
confidence: 83%
“…While a previous study has established the crucial role played by N in viral genome processing and nucleocapsid assembly (Carlson et al, 2020), to the best of our knowledge there have been no prior reports specifically highlighting its ability to elevate lentiviral spike pseudovirus infectivity. It bears mentioning that similar to existent reports (Min et al, 2020;Schubert et al, 2020;Thoms et al, 2020;Lapointe et al, 2021;Zhang et al, 2021), the Nsp1 protein presumably exerts a detrimental effect on the host cell's protein translation, as indicated by the almost imperceptible extent of infectivity observed in its case (Figure 2A).…”
Section: Discussionsupporting
confidence: 83%
“…Since no significant mutations have been observed among the protein sequences across countries, NSP1 can be potentially targeted for the discovery of drugs that can hamper the rapid progression of COVID-19. Also, major challenges in the vaccine development for the virus is to tackle the rapid mutations on the target, which can be solved by targeting NSP1 for developing the vaccine [ 54 , 55 ]. The protein sequences of NSP1 from the alpha and beta family of coronaviruses were shown to have divergence among the families (α and β), however, partially conserved nature was reported within the family.…”
Section: Resultsmentioning
confidence: 99%
“…Deciphering the mechanism by which viral-host protein-protein interactions induce the molecular pathogenesis of infection is key to identifying novel drug candidates for clinical trials (24). It has been reported that the observed differences of SARS-CoV-2 and SARS-CoV in terms of their pathogenicity and epidemiology are likely attributed to the complex interactions between various viral and host factors (35). Hence, in our study we also aimed at the identification of the human proteins interacting with P0DTC4.…”
Section: Discussionmentioning
confidence: 99%
“…Computational approaches for vaccine and drug design-as the one mentioned above-have guided the development of novel therapeutic strategies during the last decade. In silico methodology has widely been used for the identification of drugs and vaccine candidate epitopes against several bacteria and viruses including SARS-CoV-2 (2,11,27,28,35,46,48,57). Most of these studies have focused on the spike proteins and viral RNA-polymerases as potential vaccine and drug targets (46) while very few studies involve viroporin E as a vaccine or drug target candidate (11,46).…”
Section: Introductionmentioning
confidence: 99%